VIRTUAL REALITY IN MADRASAH LEARNING: EVALUATING THE IMPACT ON QUR'ANIC MEMORIZATION AND ENGAGEMENT - Hairani Lubis; MZ Muttaqien H. Lagala (CV. ADIBA AISHA AMIRA, 2025)
This study aims to evaluate the impact of using Virtual Reality (VR) technology in madrasah learning, specifically on improving Quran memorization and student engagement. Using a literature review method, this study identified and analyzed various empirical studies, academic reports, and publications related to the integration of VR in technology-based Islamic and general education. The study's results indicate that VR has significant potential to enhance immersive learning experiences, helping students visualize the context of Quranic verses, and improving focus and memory retention through multisensory stimulation. Furthermore, the use of VR in madrasah learning has been shown to increase student motivation and engagement by providing an interactive and engaging learning environment. However, challenges such as limited infrastructure, device costs, teacher training requirements, and ethical issues related to the use of technology in religious education remain significant concerns. This study emphasizes the need for a structured approach and supportive policies to ensure the effective, sustainable, and consistent implementation of VR in Quranic learning in madrasahs.